Use of Intraoperative Neuromonitoring in Surgical Treatment of Acute Presentation of Chiari I Malformation: A Case Report - Ng, Christina; Vazquez, Sima; Auerbach-Tash, Rose; Naftchi, Alexandria F.; Dominguez, Jose F.; Singh, Aalok R.; Overby, Philip; Muh, Carrie R. (Journal of Neurological Surgery Reports, 2023)
Intraoperative neuromonitoring (IONM) has been used in neurosurgical procedures to assess patient safety and minimize risk of neurological deficit. However, its use in decompressive surgeries of Chiari malformation type I (CM-I) remains a topic of debate. Here we present the case of a 5-year-old girl who presented with acute right lower extremity monoplegia after accidental self-induced hyperflexion of the neck while playing. Imaging revealed 15 mm of tonsillar ectopia with cervical and upper thoracic spinal cord edema. She was taken to surgery for a suboccipital decompression with expansile duraplasty. IONM demonstrated improvement in motor evoked potentials during the decompression. Postoperatively, she had full recovery of strength and mobility. This is a case of acute weakness after mild trauma in the setting of previously asymptomatic CM-I that showed close correlation with IONM, clinical findings, and imaging. IONM during decompressive surgery for CM-I may be useful in patients who present acutely with cervical cord edema.
Keywords: acute chiari; intraoperative neuromonitoring; decompression; chiari I malformation